Pengaruh Penyaluran Kredit, Kualitas Aset Produktif, dan Kecukupan Modal terhadap Profitabilitas Bank Perekonomian Rakyat (BPR) di Kota Bekasi Periode 2017 - 2022 - Rima, Trihanna Kezya; Prameswari, Dolly Adolina (Journal of Emerging Business Management and Entrepreneurship Studies, 2024)
This research examines the influence of Credit Distribution, Productive Asset Quality, and Capital Adequacy on the Profitability of Rural Banks (BPR). The object of this research is BPR in Bekasi City which consistently publishes financial reports on the OJK website by collecting data in the period before Covid-19 (2017-2019) and during the Covid-19 Pandemic (2020-2022). The data used was processed using SPSS using the paired t-test and multiple linear regression tests. The research results show that there are differences in BPR profitability in Bekasi City before and during the Covid-19 pandemic, credit distribution and the quality of productive assets have an influence on BPR profitability, while capital adequacy has no effect on BPR profitability in Bekasi City.